Skin Cancer Prevalence in Outdoor Workers of Ski Resorts. (28th January 2020) - Gilaberte, Yolanda; Casanova, Josep Manel; García-Malinis, Ana Julia; Arias-Santiago, Salvador; García de la Fuente, Maria Reyes; Pamiés-Gracia, Marta; Ramirez-Palomino, Javier; Ruiz-Campos, Isabel; Gracia-Cazaña, Tamara; Buendia-Eisman, Agustín
Abstract : Background . Snow reflectivity and altitude increase the exposure of ski resort workers to solar ultraviolet radiation. The aim was to assess the presence of skin cancer in ski resorts workers and compare it with other groups of outdoor workers reviewing published studies. Methods . An observational cross-sectional prospective study was conducted in the three largest ski resorts in Spain: Baqueira Beret, Lleida; Formigal, Huesca and Sierra Nevada, Granada. All outdoor workers including ski instructors were invited to participate in the study. The participants completed a validated questionnaire about sun exposure and underwent a skin examination. Results . 219 workers were included in the study (80% male; mean age 43.8 (SD 11.31) years). Actinic keratosis (AK) but no other skin cancers were detected in 32 participants (14.62%). Those with AK worked in the Southernmost ski resort, were more likely to have light colour hair, and were older and with higher photoaging grade than those without them. Conclusion . Compared to other studies, outdoor workers on ski resorts show a higher prevalence of AK than general population but a lower prevalence than other groups of outdoor workers.